Menentukan Strategi Bisnis Pada Milan Food Bandung - Stevandy, Stevandy; Amelia, Dinda; Hadiantini, Ratih (LPPM UNIBI, 2022)
The COVID-19 pandemic has significantly impacted the Micro, Small, and Medium Enterprises (MSMEs) sector in Indonesia, which serves as a cornerstone of the national economy, contributing 99.92% of total enterprises. This study focuses on Milan Food, an MSME in Bandung specializing in traditional regional snack production. The research aims to identify challenges faced by the business, including financial management, human resource management, production flow, and marketing strategies. The research employs observation and in-depth interviews with the business owner. The findings reveal that Milan Food's primary obstacles include unsystematic financial recording, suboptimal human resource management, and limited digital marketing strategies. Strengthening technology-based marketing strategies emerges as the main solution to enhance competitiveness and market reach. The study also highlights the importance of government support through training programs, product certification facilitation, and technical guidance on digitalization. This research provides strategic recommendations for Milan Food to overcome its challenges and improve operational efficiency through digital marketing, better financial management, and enhanced human resource capacity. These solutions are expected to help Milan Food sustain and grow in the modern competitive era.